2018
DOI: 10.1111/are.13592
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association analysis of salmon lice (Lepeophtheirus salmonis) resistance in a North American Atlantic salmon population

Abstract: Our objective was to detect single nucleotide polymorphisms (SNPs) associated with resistance to the salmon louse in the Saint John River aquacultural population of North American Atlantic salmon using estimated breeding values (EBVs) and 6K genotypes from the parent-generation and lice count phenotypes from the challenged, but ungenotyped, offspring-generation. In 2011 and 2012, we challenged recent smolts with approximately 100 copepodids each. Fish were euthanized once the lice reached the chalimus stages a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 43 publications
(59 reference statements)
1
11
0
Order By: Relevance
“…many genes with small effect are involved in the trait). These results agree with previous studies on sea lice resistance, where a similar genetic architecture was suggested by Tsai et al (2016), Rochus et al (2018) and Correa et al (2017) 7,10,30 for Lepeophtheirus salmonis and C. royercresseyi resistance. Recently Robledo et al (2018) 31 described three QTL in Atlantic salmon related to sea lice resistance, using RNA-seq and WGS data.…”
Section: Resultssupporting
confidence: 93%
“…many genes with small effect are involved in the trait). These results agree with previous studies on sea lice resistance, where a similar genetic architecture was suggested by Tsai et al (2016), Rochus et al (2018) and Correa et al (2017) 7,10,30 for Lepeophtheirus salmonis and C. royercresseyi resistance. Recently Robledo et al (2018) 31 described three QTL in Atlantic salmon related to sea lice resistance, using RNA-seq and WGS data.…”
Section: Resultssupporting
confidence: 93%
“…Quantitative trait loci explaining between 6% and 13% of the genetic variation in sea louse resistance (louse density on fish) have been detected in North American and Chilean populations of Atlantic salmon (Rochus et al . 2018; Robledo et al . 2019).…”
Section: What Preventative Methods Are Available?mentioning
confidence: 99%
“…It utilizes high-density SNPs distributed along the genome to determine the QTLs by statistical associations between SNP genotypes and particular phenotypes. GWAS has been successfully carried out in fish, referring to many traits, such as filet texture, fat content ( Sodeland et al, 2013 ), growth ( Gonzalez-Pena et al, 2016 ; Li et al, 2017 ), sexual maturation ( Gutierrez et al, 2015 ), disease resistance ( Liu et al, 2015 ; Zhou et al, 2017 ; Rochus et al, 2018 ; Tan et al, 2018 ), low oxygen tolerance ( Zhong et al, 2017 ), and fatty acid composition ( Horn et al, 2020 ). As for crustaceans, reports to use GWAS to discover SNPs or genes related to interesting traits are relatively less.…”
Section: Introductionmentioning
confidence: 99%